2014
DOI: 10.2147/ijn.s69822
|View full text |Cite
|
Sign up to set email alerts
|

Increased gene delivery efficiency and specificity of a lipid-based nanosystem incorporating a glycolipid

Abstract: Hepatocellular carcinoma (HCC) is the third most common cause of death related to cancer diseases worldwide. The current treatment options have many limitations and reduced success rates. In this regard, advances in gene therapy have shown promising results in novel therapeutic strategies. However, the success of gene therapy depends on the efficient and specific delivery of genetic material into target cells. In this regard, the main goal of this work was to develop a new lipid-based nanosystem formulation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For this purpose, the HNP, loaded with the fluorescent dyes coumarin-6 and nile red, and prepared with or without the GalNAc cluster, were incubated with two HCC cell lines (HepG2 and Hep3B) and one non-liver cancer cell line (DBTRG-05MG glioblastoma cell line) at 4°C (for cell binding) or at 37°C (for cell uptake). 31 , 50 After incubation, cells were analysed by flow cytometry ( Figure 5A , B and E ) and confocal microscopy ( Figure 5C and D ).
Figure 5 Evaluation of cell binding, uptake and specificity of hybrid nanosystems.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the HNP, loaded with the fluorescent dyes coumarin-6 and nile red, and prepared with or without the GalNAc cluster, were incubated with two HCC cell lines (HepG2 and Hep3B) and one non-liver cancer cell line (DBTRG-05MG glioblastoma cell line) at 4°C (for cell binding) or at 37°C (for cell uptake). 31 , 50 After incubation, cells were analysed by flow cytometry ( Figure 5A , B and E ) and confocal microscopy ( Figure 5C and D ).
Figure 5 Evaluation of cell binding, uptake and specificity of hybrid nanosystems.
…”
Section: Resultsmentioning
confidence: 99%
“…27 Several studies have shown that the use of specific ligands for this receptor allows the efficient and specific targeting of nanosystems to HCC models. 28,30,31 In this regard, Ionis Pharmaceuticals Inc. developed a triantennary N-acetylgalactosamine (GalNAc) cluster that has a high affinity for the asialoglycoprotein receptor. 32 In this study, we designed a novel delivery nanosystem, composed of PLGA nanoparticles coated with a lipid bilayer containing DSPE-PEG (2000)-GalNAc, to mediate a targeted therapeutic strategy to HCC involving the combination of selumetinib and sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…U87, A172, H4, U373, U118 cells (1×10 4 cells/well), and HMC3 cells (2×10 4 cells/well) were seeded in 96-well plates, 24 h before treatment. Cells were treated with a range of Roy concentrations (1 to 64 μM), with the vehicle control (DMSO), or with positive control (TMZ -1 to 100 μM), and further incubated for 48 h. Metabolic activity was assessed through Alamar blue ® assay [21]. Briefly, a solution of DMEM-HG medium with 10% (v/v) of a resazurin salt dye stock solution (Sigma.…”
Section: Alamar Blue ® Assaymentioning
confidence: 99%
“…Human cell lines were seeded in 96-well plates at a density of 5.0 × 10 3 cells/well (HCT116, MCF-7, and A375), and allowed to adhere for 24 h. Cells were treated with serial dilutions of compounds (ranging from 0.1 μmol/L to 50 μmol/L), for an additional 48 h. Effect on cell proliferation was measured by sulforhodamine B (SRB) assay, as described by Raimundo et al [58] and the concentration of compound that induces 50% growth inhibition (GI 50 ) was then determined for each cell line using the GraphPad Prism software version 7.0 (La Jolla, CA, USA).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Based on the GI 50 values obtained by SRB assay [58], a promising antiproliferative activity against the aforementioned cancer cells has been clearly attested for compound 11. In fact, GI 50 values for derivative 11 range from 3.55 µmol/L to 11.5 µmol/L on the tested cells, significantly lower than those observed for the remaining derivatives (Table 2).…”
Section: Anticancer Activitymentioning
confidence: 99%